Prolonged Bleeding Following Removal of Arterio-Venous Fistula Needles after Hemodialysis Therapy (Tanzania Medical Journal, 2020)
BackgroundBleeding at fistula sites in patients with end stage renal disease (ESRD) is a common and potentially serious complication that contributes to blood loss (anemia). This study aimed to determine the factors that influence prolonged bleeding at fistula puncture sites following removal of fistula needles.MethodsThis was a descriptive cross-sectional study. We consecutively enrolled patients who underwent maintenance hemodialysis between May and October 2017 at Muhimbili National Hospital and Access Dialysis Centre in Dar es Salaam, Tanzania. A case report form (CRF) was used for data collection. Prolonged bleeding was assessed by measuring activated partial thromboplastin time (aPTT) and compression time (CT). Descriptive statistics and regression analysis were used to assess the association between factors and tease out the independent factors associated with prolonged bleeding at fistula puncture site. A two-tailed p-value <0.05 was used as a cut-off for statistical significance.ResultsOne hundred and fifteen patients were recruited for the study whereby 81(70.4%) of participants had elevated aPTT (> 31 seconds) and 4 (3.5%) had prolonged compression time (> 15 minutes). The mean aPTT and compression time of the participants were 42 ± 17.6 seconds and 5 ± 2.9 minutes respectively. Over half of participants 67(58.2%) had normal compression time (? 15 minutes). Elevated serum urea levels (> 7.4mmol/L) was the only factor significantly associated with elevated aPTT (OR=4.143 95% C.I (1.021-16.810), p=0.047).ConclusionThe findings have demonstrated that elevated serum urea levels are significantly associated with prolonged bleeding time following removal of Arterio-Venous fistula needles after completion of a hemodialysis therapy session. This study suggests that, in hemodialysis procedure where a fixed dose of heparin is generalized to all patients there is a chance of exceeding the individual’s requirements.RecommendationsSerum urea levels should be factored in when gauging the individual risk of arterio-venous fistula site bleeding for patients using heparin for anticoagulation during hemodialysis. Further studies with large sample sizes are recommended to elucidate how other predisposing factors may affect A-V fistula bleeding.Keywords: Hemodialysis, heparin, prolonged bleeding, urea reduction ratio, A-V Fistula, aPTT, Compression time, blood urea.